Rancang Bangun Mesin Pemotong Rumput Berbasis Sistem Kontrol - Mazwan Mazwan; Ari Kurniawan; Ahmad Fauzi Pohan; Kholis Gunawan (Piston: Jurnal Teknologi, 2026)
Manual grass cutting still requires considerable labor and has a low level of efficiency. Therefore, a device is needed to improve the effectiveness and efficiency of the grass-cutting process. This study aims to design and test a grass-cutting machine based on a control system equipped with a blade drive mechanism and a track-based mobility system. The research method included mechanical design, system assembly, and performance testing of the device. Testing was carried out on several main components, namely the blade drive mechanism, the track tensioning system, and the safety of the track shoe under various terrain conditions. The test results showed that the blade drive mechanism worked properly, in which the blade could rotate optimally when the linear actuator piston stroke reached 60 mm. The testing of the track tensioning system indicated that a tensioning distance of 6 cm was the most stable condition, as the track did not detach from the sprocket during operation. In addition, testing of the track shoe on flat and inclined roads over a distance of 15 meters showed that the system was able to provide good movement stability and traction without causing damage to the track components. Overall, the designed grass-cutting machine was able to operate stably and has the potential to be used under various terrain conditions in the grass-cutting process.